2013
DOI: 10.1016/j.jacc.2013.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipase A2-IIA and Cardiovascular Disease

Abstract: ObjectivesThis study sought to investigate the role of secretory phospholipase A2 (sPLA2)-IIA in cardiovascular disease.BackgroundHigher circulating levels of sPLA2-IIA mass or sPLA2 enzyme activity have been associated with increased risk of cardiovascular events. However, it is not clear if this association is causal. A recent phase III clinical trial of an sPLA2 inhibitor (varespladib) was stopped prematurely for lack of efficacy.MethodsWe conducted a Mendelian randomization meta-analysis of 19 general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 23 publications
5
71
0
1
Order By: Relevance
“…A recent meta-analysis ( 36 ), which included 79,036 participants with or without coronary artery disease from 32 prospective studies, showed that Lp-PLA 2 activity and mass each had a continuous association with the risk for coronary artery disease; as similarly, the present study showed positive correlation between Lp-PLA 2 and CVD risk factors . On the other hand, Holmes et al ( 38 ) suggested that reducing secretory phospholipase A 2 (sPLA 2 )-IIA mass is unlikely to be a useful therapeutic goal for preventing cardiovascular events , which is associated with increased risk of incident and recurrence of major vascular events. PLA2G2A had large and specifi c effects on circulating sPLA 2 -IIA mass and a small-to-modest effect on sPLA 2 enzyme activity ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis ( 36 ), which included 79,036 participants with or without coronary artery disease from 32 prospective studies, showed that Lp-PLA 2 activity and mass each had a continuous association with the risk for coronary artery disease; as similarly, the present study showed positive correlation between Lp-PLA 2 and CVD risk factors . On the other hand, Holmes et al ( 38 ) suggested that reducing secretory phospholipase A 2 (sPLA 2 )-IIA mass is unlikely to be a useful therapeutic goal for preventing cardiovascular events , which is associated with increased risk of incident and recurrence of major vascular events. PLA2G2A had large and specifi c effects on circulating sPLA 2 -IIA mass and a small-to-modest effect on sPLA 2 enzyme activity ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Holmes et al ( 38 ) suggested that reducing secretory phospholipase A 2 (sPLA 2 )-IIA mass is unlikely to be a useful therapeutic goal for preventing cardiovascular events , which is associated with increased risk of incident and recurrence of major vascular events. PLA2G2A had large and specifi c effects on circulating sPLA 2 -IIA mass and a small-to-modest effect on sPLA 2 enzyme activity ( 38 ). In addition, sPLA 2 inhibitor, called varespladib, was not a useful strategy to reduce adverse cardiovascular outcomes after acute coronary syndrome ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…82 In a short-term clinical outcomes trial of patients with ACS treated with atorvastatin, varespladib methyl increased acute MIs resulting in early termination of this trial. 83 Holmes et al 84 investigated the validity of sPLA 2 -IIA as a therapeutic target, and colleagues who conducted a Mendelian randomization meta-analysis that included 10 ACS cohorts (2520 recurrent major vascular events in 18 355 individuals) investigated observational studies between the PLA2G2A rs11573156 variant that encodes the sPLA 2 -IIA isoenzyme and cardiovascular events. 84 In the ACS cohorts, the PLA2G2A rs11573156 C allele was associated with 44% lower circulating sPLA 2 -IIA mass and 3% sPLA 2 enzyme activity per C allele.…”
Section: Additional Lipoprotein-related Biomarkers and Therapeutic Tamentioning
confidence: 99%
“…83 Holmes et al 84 investigated the validity of sPLA 2 -IIA as a therapeutic target, and colleagues who conducted a Mendelian randomization meta-analysis that included 10 ACS cohorts (2520 recurrent major vascular events in 18 355 individuals) investigated observational studies between the PLA2G2A rs11573156 variant that encodes the sPLA 2 -IIA isoenzyme and cardiovascular events. 84 In the ACS cohorts, the PLA2G2A rs11573156 C allele was associated with 44% lower circulating sPLA 2 -IIA mass and 3% sPLA 2 enzyme activity per C allele. The odds ratio for major vascular events per rs11573156 C allele was 0.96 (95% confidence interval, 0.90-1.03) in ACS cohorts.…”
Section: Additional Lipoprotein-related Biomarkers and Therapeutic Tamentioning
confidence: 99%
“…Cependant, les espoirs portant sur la sPLA2 comme une cible dans les maladies cardiovasculaires ont été atténués par la publication récente d'une étude de grande envergure qui a regroupé plus de 30 cohortes totalisant environ 100 000 sujets. Les auteurs ont montré qu'un polymorphisme du gène codant pour la PLA2 du groupe IIA (rs11573156) était certes associé à une diminution de la sPLA2 plasmatique (taux et l'activité) mais, malheureusement, n'était pas associé à une augmentation du risque cardiovasculaire [36].…”
Section: Lp-pla2 Et Risque Cardiovasculaireunclassified